Role of Glycolysis and Nitric Oxide Pathway Crosstalk in Macrophages in Atherosclerosis - Kotlyarov, Stanislav (Current Medicinal Chemistry, 2025)
Atherosclerosis is a complex multifactorial process that occurs in the vascular wall over many years and is responsible for a number of major diseases that affect quality of life and prognosis. A growing body of evidence supports the notion that immune mechanisms underlie atherogenesis. Macrophages are considered one of the key participants in atherogenesis, but their role in this process is multifaceted, which is largely due to the peculiarities of their cellular metabolism. Glycolysis is not only an important metabolic pathway in macrophages, but is also associated with their immune functions. Glycolysis in macrophages has complex regulatory pathways and is cross-linked with nitric oxide, which together determine the immune function of these cells. Thus, the immune and metabolic links underlying atherogenesis are of research and clinical interest in terms of their potential therapeutic opportunities.
Keywords: Atherosclerosis